Inovasi Kurikulum Berbasis Karakter dan Kontekstual untuk Transformasi Mutu Pendidikan Anak Usia Dini - Alya Arthamevia Putri; Salma Kusuma Ningrum; Fetty Ernawati (Edu Berkah Khatulistiwa, 2026)
The purpose of this research is to analyze the model of curriculum innovation management based on character and contextual approaches in improving the quality of early childhood education (PAUD). The background of this research is based on the suboptimal implementation of the Independent Curriculum, particularly in systematically integrating character values and contextual approaches in the learning process. This research uses a qualitative approach with a literature study type. Data was obtained from various scientific sources, including journals, with a minimum focus on SINTA 5 ranked journal, as these journals have undergone a process that meets established scientific standards. Additionally, data was obtained from books and previous research relevant to the topic discussed. Data collection techniques are carried out through documentation studies, while data analysis uses qualitative descriptive analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. Research results show that character-based and contextual curriculum management innovation plays a significant role in creating learning that is more meaningful, adaptive, and relevant to children's lives. The integration of character values through habituation, role modeling, and the utilization of local wisdom has been proven to support the holistic formation of children's character. However, its implementation still faces various obstacles, such as limited teacher competence, infrastructure, and less than optimal environmental support. Therefore, innovative strategies are needed in the form of improving teacher competence, strengthening collaboration between parents and the community, and optimizing the use of the environment as a learning resource.